ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SEKOLAH MENENGAH PERTAMA PADA MATERI ALJABAR - Haniatusaadah, Siti; Basir, Mochamad Abdul (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Mathematical communication skills are one of the basic abilities that students need to have. With mathematical communication, it is expected that the ability of students' mathematical concepts can improve. The subjects in this study were Grade VII students of MTs Assyafi'iyyah Talun, District of Kayen, Pati Regency. The purpose of this research is to find out the students' mathematical communication skills in algebraic material. Descriptive research with a qualitative approach is the type of research used by researchers. Data collection used is a test and documentation method. Based on the results of data analysis, students' mathematical communication skills on algebraic material are obtained: (a) the ability to express real objects, situations, and daily events into the form of mathematical models including high categories; (b) the ability to represent real objects, images, and diagrams in the form of mathematical models included in the high category; (c) the ability to express daily events in the form of mathematical models included in the medium category; d) the ability to express a mathematical model back into one's own language is included in the medium category; (d) the ability to describe or represent real objects in the form of mathematical models included in the medium category.